0578 Incident Hypertension Rates in OSA Identified Using American Academy Of Sleep Medicine (AASM) Hypopnea Criteria, but Misclassified by Medicare (CMS) Hypopnea Definition. (27th May 2020) - Budhiraja, R; Javaheri, S; Berry, R B; Parthasarathy, S; Quan, S F
Abstract: Introduction: The impact of not treating OSA identified using AASM standards (hypopneas scored using a minimum 3% O2 desaturation or arousal), but misclassified by CMS standards (hypopneas scored only if minimum 4% O2 desaturation) remains unclear. This analysis determined the 5 year incident hypertension rates using the new 2018 ACC/AHA blood pressure (BP) guidelines in these individuals. Methods: Data were analyzed from all Sleep Heart Health Study exam 2 study participants (N=1219) who were normotensive (BP≤120/80) at exam 1. The apnea hypopnea index (AHI) at exam 1 was classified into 4 categories of OSA severity: <5, 5 ≤15, 15 ≤30 and ≥30/hour using both the AASM or CMS definitions. Three definitions of hypertension were used: Elevated BP (>120/80), Stage 1 (>130/80) and Stage 2 (>140/90) to determine incidence rates at exam 2. Results: Five year follow-up data were available for 476 participants classified as having OSA (AHI ≥5) by AASM criteria, but not by CMS standards at exam 1. Incident hypertension rates in these misclassified participants for ACC/AHA defined BP categories were 15% (Elevated BP), 15% (Stage 1) and 6% (Stage 2). 4% of normotensive participants used hypertensive medications. Overall incidence rate of at least an elevated BP was 40% (191/476) in those with OSA defined using AASM, but not by CMS criteria and 17% (191/1219) of the overall population at risk. In comparison to those with incident hypertension and OSA identified by CMS standards, BMI (27.7 vs 30.1 kg/m 2, p<.001) and % men were lower (45 vs 58%, p=.012), but age and race were not different. Conclusion: Use of the CMS hypopnea definition as a component of the AHI resulted in the failure to identify a significant number of individuals with OSA who eventually developed hypertension and could have benefited from earlier diagnosis and treatment. Support: HL53938